IMPLEMENTASI ROUTING PROTOKOL BORDER GATEWAY PROTOCOL (BGP) PADA ROUTER MIKROTIK RB 2011 DI KOMINFO KABUPATEN SOLOK SELATAN - Eko Kurniawanto Putra (ITP Press, 2021)
The development of digital technology when at this time is very rapid, to accompany this supporting factor of digital technology also must be able to support this development supporting factors in the form of computer network installation. For example, South Solok Regency which is in the midst of tidying up with all existing services, can join in a computer network that can be centrally controlled. To overcome this problem, a network scale MAN (Metropolitan Area Network) was implemented in South Solok Regency. The model of determining the path (routing) is very influential, to connect all official services is BGP (Border Gateway Protocol) routing which supports network implementation on a large scale. Quality Routing Implementation of BGP can be tested with QoS that maximizes digital technology available in South Solok Regency. centralized control of the Communication and Information Service (KOMINFO) makes the process of implementing digital technology and BGP routing helping to make handling of network problems easier.